Determinants of Food Safety Practices in Food Handlers: A Literature Review - Suyitno, Suyitno; Suryani, Dyah; Jannah, Arihni Arihatal (PROMOTOR, 2024)
Food safety is an effort to ensure food is safe for consumption, free from physical, chemical, and biological hazards, so that there is no risk of it causing disease if consumed. Creating these conditions is closely related to food safety practices among food handlers. It is necessary to control food safety practices that can be carried out if the determining factors are known in advance. Thus, this study aims to summarize and describe the determinants of food safety practices among food handlers based on previous research articles. This study uses the literature review method to identify research articles that are relevant to the research objectives. The keywords used are "food safety practices" and "food handler" from the PubMed, SAGE, and Wiley databases. Search articles using the PRISMA method. Of the 974 identified articles, 10 met the inclusion criteria and research objectives. The results obtained identified 12 variables related to food safety practices, namely food safety knowledge (7 articles), education level (6 articles), food safety training/courses (5 articles), attitudes towards food safety (4 articles), household income/wealth household (3 articles), work experience (2 articles), sanitation facilities (2 articles), work status (1 article), marital status (1 article), ethnicity (1 article), and registered food seller (1 article). It can be concluded that the dominant determinants of food safety practices among food handlers are knowledge of food safety, level of education, food safety training or courses, attitudes towards food safety, household income or wealth, work experience, and sanitation facilities.